2016
DOI: 10.1038/srep27364
|View full text |Cite
|
Sign up to set email alerts
|

The ghost sex-life of the paedogenetic beetle Micromalthus debilis

Abstract: Genetic and sexual systems can be evolutionarily dynamic within and among clades. However, identifying the processes responsible for switches between, for instance, sexual and asexual reproduction, or cyclic and non-cyclic life histories remains challenging. When animals evolve parthenogenetic reproduction, information about the sexual mating system becomes lost. Here we report an extraordinary case where we have been able to resurrect sexual adults in a species of beetle that reproduces by parthenogenetic pae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…Parthenogenesis may have evolved as an escape route from maintenance of sex (males), i.e., development of eggs without fertilization and female-only populations (Schwander et al, 2010;Elzinga et al, 2011;Perotti et al, 2016). In evolutionary time, mating costs that limit female fitness influence the evolution of mating systems, in particular the transition from sexual to asexual reproduction (Gerber & Kokko, 2016;Burke & Bonduriansky, 2017).…”
Section: The Role Of Immobility In Fmfmentioning
confidence: 99%
“…Parthenogenesis may have evolved as an escape route from maintenance of sex (males), i.e., development of eggs without fertilization and female-only populations (Schwander et al, 2010;Elzinga et al, 2011;Perotti et al, 2016). In evolutionary time, mating costs that limit female fitness influence the evolution of mating systems, in particular the transition from sexual to asexual reproduction (Gerber & Kokko, 2016;Burke & Bonduriansky, 2017).…”
Section: The Role Of Immobility In Fmfmentioning
confidence: 99%
“…In the smaller suborder Archostemata, Micromalthus debilis LeConte, 1878 (Micromalthidae) with its extremely bizarre life cycle usually reproduces by thelytokous parthenogenesis, but it also has a rare arrhenotokous phase that apparently represents an evolutionary dead end (Pollock & Normark, ). During the latter process, the emerging male larva, which never develops into an adult male under normal conditions, obligately devours its mother, another (paedogenetic) larva (Perotti, Young, & Braig, ). Nevertheless, adult males in this species can be artificially obtained using intensive heat treatment of the male larvae.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, adult males in this species can be artificially obtained using intensive heat treatment of the male larvae. However, these males are still non‐functional, and females of M. debilis exhibit sex‐role reversal of mating behavior, intensively competing for males and initiating copulation with them (Perotti et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a very interesting topic for future studies is the examination of the presence of other intracellular and symbiotic bacteria (like Cardinium, Spiroplasma, Rickettsia), in Coleoptera and their relations, both with the host and Wolbachia. So far, only three studies have found Wolbachia with Rickettsia and/or Spiroplasma together in beetle hosts (Majerus et al, 2000;Weinert et al, 2007;Toju & Fukatsu 2011;White et al, 2015;Perotti et al, 2016;Bili et al, 2016;Dudek et al, 2017). Preliminary results suggest that there is some balance in the number of these bacteria, probably caused by competition within host cells (Goto et al, 2006).…”
Section: Current Gaps and Future Endeavorsmentioning
confidence: 93%